Scorias spongiosa Polysaccharides Promote the Antioxidant and Anti-Inflammatory Capacity and Its Effect on Intestinal Microbiota in Mice - Xu, Yingyin; Zhang, Zhiyuan; Feng, Huiyu; Tang, Jie; Peng, Weihong; Chen, Ying; Zhou, Jie; Wang, Yong (Frontiers in Microbiology, 2022)
Scorias spongiosa, as an edible fungus, has multiple health benefits. However, the effects of Scorias spongiosa on intestinal health are rarely explored. Hence, our study aims to elaborate on the influences of Scorias spongiosa polysaccharides (SSPs) on antioxidant, anti-inflammatory and intestinal microflora in C57BL/6J mice. In the present study, 18 male mice were randomly distributed into three groups: (1) Control group (CON); (2) Low dose SSPs group (LSSP); (3) High dose SSPs group (HSSP). After 14-day administration, the jejunum and serum samples were collected for detection. The results showed that SSPs exert no effects on the growth performance of mice regardless of doses. Meanwhile, SSPs administration reduced the serum pro-inflammatory cytokines and elevated the anti-inflammatory cytokines. Moreover, the antioxidant capacity was elevated by SSPs administration, as evidenced by the increased contents of T-AOC, GSH-Px and the decreased content of MDA. Mechanistically, the administration of SSPs enhanced the protein abundances of p-Nrf2, Keap1 and HO-1 in mice. The results of 16S rDNA demonstrated that the microbial community and composition were altered by SSPs administration. To summarize, SSPs benefit intestinal health in C57BL/6J mice via a mechanism that involves elevating antioxidant and anti-inflammatory activities and regulating intestinal microbiota.